Hot for a cowboy - Redford, Kim (Redford, Kim. Smokin' hot cowboys., 2019)
Eden Rafferty has lost it all: big-time career, high profile marriage, and just about everything she owns. Coming back to Wildcat Bluff with her tail between her legs, the only person who can help her heal is cowboy firefighter Shane Taggart. But nothing is simple, and their high-octane past is just the beginning of their current problems.. --p. 4 of cover